Pemberdayaan Ekonomi Masyarakat Berbasis Teknologi Irigasi Tetes Dengan Energi Hijau (Energi Surya) Untuk Meningkatkan Produksi Tanaman Hortikultura Pada Kelompok Tani Bethesda Desa Penfui Timur Kabupaten Kupang - Taus, Desitriana; Levis, Leta Ravael; Nainiti, Selfius P.N.; Nendissa, Doppy Roy (Undana Press, 2024)
Drip irrigation can be the right choice to overcome the problem of drought, especially in the growth of fruit and vegetable crops during the long dry season, because long dry seasons cause the land to have little water supply. This research was carried out in East Penfui Village, Central Kupang District, Kupang Regency from March to April. The aim is to understand the process of community empowerment in implementing drip irrigation technology to increase horticultural crop production. This research is a qualitative research. The reason for choosing this technology is because this place still lacks water, and the Bethesda farming group has used drip irrigation with green energy (solar energy). The data collection method uses in-depth interviews. The data analysis used is the Miles and Huberman Interactive model. This data processing is carried out interactively and continues continuously until completion at a certain stage, so that the data obtained is saturated. The results of the research in empowering drip irrigation technology in the Bethesda farmer group were that the following process was carried out: 1) socialization about drip irrigation, 2) techniques for making drip irrigation, 3) selection of soil type, 4) selection of plant types, 5) determination of the use of irrigation technology drip, 6) preparation of funds, 7) labor, 8) farmer field school (SLP) regarding drip irrigation. The community enthusiastically responded well and agreed to the installation of this drip irrigation technology system because it could help them overcome the problem of water shortages. The group members understand the benefits of drip irrigation and are skilled in installing irrigation hoses, installing irrigation pipes, spreading mulch and of course can become more skilled in planting horticultural plants.